2015
DOI: 10.4102/curationis.v38i2.1522
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of homosexual patients’ access to primary health care services in Umlazi, KwaZulu-Natal

Abstract: BackgroundHomosexual patients are affected by social factors in their environment, and as a result may not have easy access to existing health care services. Prejudice against homosexuality and homosexual patients remains a barrier to them seeking appropriate health care. The concern is that lesbians and gays might delay or avoid seeking health care when they need it because of past discrimination or perceived homophobia within the health care thereby putting their health at risk.Aim of the studyThe aim of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 20 publications
2
12
0
5
Order By: Relevance
“…Many lesbian women, for example, are afraid to reveal their sexual orientation during gynecological care and are not assisted in the health services 2 . When gays go to the health services and verbalize their sexual orientation, they suffer stigmas and prejudice deriving from the AIDS-homosexuality association 3 .Transvestites and transsexuals experience even greater discriminations in the access to the health services, either in the use of their social name or in the guarantee of the transsexualizing process 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Many lesbian women, for example, are afraid to reveal their sexual orientation during gynecological care and are not assisted in the health services 2 . When gays go to the health services and verbalize their sexual orientation, they suffer stigmas and prejudice deriving from the AIDS-homosexuality association 3 .Transvestites and transsexuals experience even greater discriminations in the access to the health services, either in the use of their social name or in the guarantee of the transsexualizing process 4 .…”
Section: Introductionmentioning
confidence: 99%
“…LGBTI people are still subject to discrimination, stigmatization, humiliation, verbal assault, and neglect by health professionals, all of which make them reluctant to disclose their sexual orientations to health professionals (Beycan Ekitli & Çam, 2017). Cele, Sibiya, and Sokhela (2015) studied the difficulties that LGBTI people encounter while receiving healthcare services and reported that LGBTI people complained about being judged by the way they dress, talk, and walk; being judged by their personalities; being rejected by other patients; and being given religious warnings and advice by health professionals. Studies conducted with nurses have reported attitudes such as refusing to care for LGBTI patients, abandoning and avoiding them, and regarding them as perverts or deviants (Beycan Ekitli & Çam, 2017; Hotun Şahin & Bilgiç, 2016).…”
mentioning
confidence: 99%
“…20,34,57 There is a pervasive societal argument that sexual and gender minority is un-African, thus silently punishing those who transgress this view and relegating them to the margins. 46,58…”
Section: Resultsmentioning
confidence: 99%